Incorporation of starch or starch-xanthan mixtures in renneted milk systems to improve yield and texture - Totosaus, Alfonso; Pineda-Calderón, Lucia (Revista Colombiana de Investigaciones Agroindustriales, 2021)
In order to improve the yield and texture of fresh type cheese, different types of starch or their combination with xanthan gum were tested in a model system, to determine the effect of these ingredients on the yield, whey release, syneresis, and moisture, as well as the texture parameter as hardness, adhesiveness, cohesiveness, and springiness. Wheat starch, potato starch, Gelamil modified starch and Nifragel modified starch was employed at 5% (W7v), or their combination with xanthan gum (1% (w/v) in a rennet milk system. To employ starches with xanthan gum resulted in higher yields and lower whey released volume, besides present lower syneresis and more moisture, due to the water retention properties of the ingredients. This attribute was also reflected in harder but more adhesive and less cohesive and elastic texture, due to the reduced water mobility in the system by the action of the starch and xanthan gum. Under the experimental conditions, native starches with xanthan gum have the better performance, since the rennet milk systems imply a precipitated gel with a casein matrix with net charge close to its isoelectric point, a characteristic that makes difficult the interaction with other hydrocolloids, and hence ingredients like starches that act as fillers with the xanthan gum have a strong impact on moisture retention in these types of foods.